Distribution of Ploidy Level on Adiantumdiaphanum Blume at Various Altitudes in Probolinggo - Amelia, Ade Rezi; Fauzi, Ahmad (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2018)
Ferns are indicated could become polyploid organism due to altitude effect. In this research, the distribution of ploidy level on AdiantumdiaphanumBlume based on difference altitude was studied. This study was a survey research conducted in Probolinggo Regency which aims studying the effect of altitude on ploidy level in A. diaphanumBlume. Leces (50 masl), Lumbang (460 masl), and Sukapura (820 masl) were the tree research sampling areas that represent low, medium, and highland location, respectively. The determination of ploidy level was conducted by counting the chromosome number of cells root tips. The results showed that all ferns found in the medium and lowland were diploid organisms, whereas all ferns found in the highlands were triploid organism.